Development of Ultra-Fast Silicon Switches for Active X-Band High Power RF Compression Systems - Jiquan Guo; Tantawi, S.G. (Proceedings of the 2005 Particle Accelerator Conference, 2005)
In this paper, we present the recent results of our research on the high power ultra-fast silicon RF switches. This switch is composed of a group of PIN diodes on a high purity SOI (silicon on oxide) wafer. The wafer is inserted into a cylindrical waveguide under TE01 mode, performing switching by injecting carriers into the bulk silicon. Our current design use a CMOS compatible process and the device was fabricated at SNF(Stanford Nanofabrication Facility). This design is able to achieve sub-100ns switching time, while the switching speed can be improved further with 3-D device structure and faster circuit. Power handling capacity of the switch is at the level of 10MW. The switch was designed for active X-band RF pulse compression systems - especially for NLC, but it is also possible to be modified for other applications and other frequencies such as L-band.